2020
DOI: 10.3390/md18120603
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Human CYP1A2 and CYP3A4 Inhibitors from Seaweed In Silico and In Vitro

Abstract: Phenolic compounds and carotenoids are potential inhibitors of cytochrome P450s. Sixteen known compounds, phenolic compounds and carotenoids from seaweed were examined for potential inhibitory capacity against CYP1A2 and CYP3A4 in silico and in vitro. Morin, quercetin, and fucoxanthin inhibited the enzyme activity of CYP1A2 and CYP3A4 in a dose-dependent manner. The IC50 values of morin, quercetin, and fucoxanthin were 41.8, 22.5, and 30.3 μM for CYP1A2 and 86.6, 16.1, and 24.4 μM for CYP3A4, respectively. Sip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Our results are in agreement with an experimental study mentioning that resveratrol modified the metabolism of aripiprazole by CYP2D6 and CYP3A4 [64]. The predicted inhibitory activity of quercetin on CYP1A2 is supported by a previous study [65] showing that quercetin is able to change the metabolism of melatonin by CYP1A2. Quercetin was also reported to be a strong inhibitor of CYP2D6 and a moderate inhibitor of CYP3A4 [66].…”
Section: Computational Pharmacokinetics and Pharmacogenomics Profiles Of Natural Compoundssupporting
confidence: 92%
“…Our results are in agreement with an experimental study mentioning that resveratrol modified the metabolism of aripiprazole by CYP2D6 and CYP3A4 [64]. The predicted inhibitory activity of quercetin on CYP1A2 is supported by a previous study [65] showing that quercetin is able to change the metabolism of melatonin by CYP1A2. Quercetin was also reported to be a strong inhibitor of CYP2D6 and a moderate inhibitor of CYP3A4 [66].…”
Section: Computational Pharmacokinetics and Pharmacogenomics Profiles Of Natural Compoundssupporting
confidence: 92%
“…The results showed that cineole and its derivatives had no predicted inhibitory effects as the predicted value was 0 ( Table 2 ). Importantly, ketoconazole (positive control) was predicted accurately with a value of one, indicating that it is a potent CYP3A4 inhibitor [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Commercially, FX and SX are sold as health supplements because these compounds are believed to possess a variety of health benefits [ 20 , 21 , 22 ]. However, in previous studies, FX inhibited the activity of CYP1A2 and CYP3A4 with an IC50 of 30.3 μM and 24.4 μM, respectively [ 33 , 34 , 35 ]. These CYPs are responsible for the metabolism of more than 60% of commonly prescribed drugs [ 36 ].…”
Section: Discussionmentioning
confidence: 97%
“…Ultra-pure argon (99.99%), nitrogen (99.99%), and carbon dioxide were supplied from Daechang Gas (Songha-dong, Gwangju, South Korea). Fucoxanthin (FX) and siphonaxanthin (SX) were extracted and purified from sporophyll of Undaria pinnatifida and Codium fragile , respectively, for a previous study [ 35 ].…”
Section: Methodsmentioning
confidence: 99%